A laser etched zinc ion microbattery with excellent flexibility and self-healability. Issue 9 (20th July 2020) - Du, Xiaoyu; Shi, Junjie; Chen, Zhicheng; Ni, Tong; Li, Jiaxin; Ruan, Limin; Zeng, Wei; Cheng, Feng; Yue, Yang; Wang, Siliang
Abstract : Aqueous zinc ion microbatteries (ZIMBs) exhibit excellent flexibility and self-healability. Abstract : With the development of wearable and integrated electronic devices, the demand for microbatteries (MBs) with the characteristics of miniaturization and easy integration continues to increase. Currently, a few organic electrolyte-based lithium ion MBs (LIMBs) have been reported, but the intrinsic drawbacks of poor safety and high cost constrain their practical applications. In addition, the electrochemical performance drops sharply after being bent or damaged during use, and thus the reliability and stability of such LIMBs are restricted. To overcome the above problems, a laser etched zinc ion MB (ZIMB) with the multi-walled carbon nanotubes–manganese dioxide (MWCNTs–MnO2 ) cathode, MWCNTs–Zn anode, zinc sulfate–manganese sulfate–polyacrylamide (ZnSO4 –MnSO4 –PAM) hydrogel electrolyte and modified polyurethane (PU) protective shell is achieved. The hydrogel electrolyte and cheap zinc anode contribute to the high safety and low cost of the device. The self-healing PU protective shell contributes to the reliability and stability illustrated by the excellent flexibility and self-healability of the device, e.g. the capacity reduces little under a large bending angle of 120°, and the capacity retention is up to 90.2% after the 5 th self-healing cycle. This study provides a novel option to design new generation micro energy storage devices with good reliability and stability.